The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/5082594
|View full text |Cite
|
Sign up to set email alerts
|

Research on Influencing Factors of Adoption Behavior of Mobile Readers Based on Meta-Analysis

Abstract: Many scholars have conducted extensive research on the adoption behavior of mobile readers, and there are obvious differences in the degree and direction of conclusions drawn from different individual studies. In this study, a meta-analysis method was used to comprehensively analyze a total of 74,964 independent samples of 31 relevant empirical research documents at home and abroad. The results show that the main influencing factors of mobile reading are perceived usefulness, perceived ease of use, perceived m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This aligns with our proposed theoretical model. Specifically, research hypothesis H1 confirms that adopting virtual dynamic aesthetic decorations created with AR technology positively impacts users' perceived ease of use, consistent with previous studies [151,152,231,232]. This reveals that in the live streaming industry, aside from attracting users through traditional advertising and promoting more excellent live broadcasts to meet entertainment needs [233,234], incorporating AR technology to design interactive dynamic decorations with aesthetic significance can lower user barriers and enhance usability for consumers or potential users.…”
Section: The Value Enhancement Role Of Ar Technology In Network Enter...supporting
confidence: 83%
See 1 more Smart Citation
“…This aligns with our proposed theoretical model. Specifically, research hypothesis H1 confirms that adopting virtual dynamic aesthetic decorations created with AR technology positively impacts users' perceived ease of use, consistent with previous studies [151,152,231,232]. This reveals that in the live streaming industry, aside from attracting users through traditional advertising and promoting more excellent live broadcasts to meet entertainment needs [233,234], incorporating AR technology to design interactive dynamic decorations with aesthetic significance can lower user barriers and enhance usability for consumers or potential users.…”
Section: The Value Enhancement Role Of Ar Technology In Network Enter...supporting
confidence: 83%
“…Nia and Shokouhyar (2020) further support this point, indicating that website aesthetics directly and positively impact perceived usefulness, usability and privacy, thereby influencing trust [151]. Interface design has a significant positive impact on perceived usability, demonstrating the critical role of aesthetics in enhancing usability [152]. The synthesis of these references collectively demonstrate the positive impact of aesthetics on perceived usability.…”
Section: Research Methods and Hypothesismentioning
confidence: 92%
“…During data extraction, it was found that there are variables with different names but these variables have the same connotations and meanings. Based on the practice of merging variables in a previous study (Zhou et al , 2021), the researchers also merged these variables into one standard name each for the variables. Behaviour or behavioural intention, system use, intention use and digital library use were classified as IU.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers used discrimination validity and correlation matrix tables of selected studies for extracting data. The researchers provided the discrimination validity table (Kaushik, 2022; Zhou et al , 2021), and correlation matrix in empirical studies provided the value of the correlation coefficient (Kaushik, 2022). Therefore, they used these two tables for extracting relevant data from the selected studies.…”
Section: Data Analysis Processmentioning
confidence: 99%